Characterization of the Attitudes of Undergraduate Mathematics Students towards Numerical Methods - Yolanda Haydeé Montero; María Eugenia Pedrosa; Mercedes Susana Astiz; Silvia Lucía Vilanova (Universidad Autónoma de Baja California, 2014)
With the purpose of improving the process of teaching and learning numerical methods in undergraduate students majoring in Mathematics in the School of Natural and Exact Sciences of the National University of Mar de Plata (Argentina), we decided to investigate possible factors that could adversely affect this process. We found it necessary to examine students' attitudes, since they can have an important effect on immediate academic performance. The study involved a design stage, pilot testing, instrument validation, analysis of the consistency of responses through cluster classification by variables, a descriptive stage and an analysis of possible relationships between the variables studied. The results show that students have a moderately positive attitude towards the subject, in which pleasure, valuation and anxiety play a key role.